2015
DOI: 10.1002/nau.22818
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical treatment with cis-urocanic acid improves bladder function in rat model of acute bladder inflammation

Abstract: Intravesical administration of cis-UCA was able to partially recover bladder function impaired by chemical irritation. Cis-UCA may offer a novel intravesical treatment option in some inflammatory conditions of the bladder. Neurourol. Urodynam. 35:786-791, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…The second was an ovalbumin-induced ocular allergy model in which cis-UCA, like olopatadine, could significantly inhibit conjunctival vascular leakage. For treatment of acute hydrochloride acideinduced bladder inflammation, 2% cis-UCA as an intravesical infusion was as efficient as a proven treatment, 0.5% hyaluronic acid, in improving bladder function in rats (Konkol et al, 2016). Histopathological studies suggested that the anti-inflammatory actions of cis-UCA were due to its tissueprotective properties in reducing the detrimental activity of acute phase immune cells already present in the bladder, without affecting the infiltration of inflammatory cells.…”
Section: Introductionmentioning
confidence: 94%
“…The second was an ovalbumin-induced ocular allergy model in which cis-UCA, like olopatadine, could significantly inhibit conjunctival vascular leakage. For treatment of acute hydrochloride acideinduced bladder inflammation, 2% cis-UCA as an intravesical infusion was as efficient as a proven treatment, 0.5% hyaluronic acid, in improving bladder function in rats (Konkol et al, 2016). Histopathological studies suggested that the anti-inflammatory actions of cis-UCA were due to its tissueprotective properties in reducing the detrimental activity of acute phase immune cells already present in the bladder, without affecting the infiltration of inflammatory cells.…”
Section: Introductionmentioning
confidence: 94%
“…Despite the fact that the effects of cis-UCA may be cell type-dependent, many in vivo and in vitro studies have revealed its anti-inflammatory properties and potential to protect from cell injury. [25][26][27][28] Our previous studies have revealed that cis-UCA is well tolerated by human corneal epithelial (HCE) and conjunctival epithelial (HCEC) cells. 29 Additionally, pretreatment with cis-UCA prevents cell death and the secretion of IL-8 and IL-6 in UV-B-induced HCE and HCEC cells.…”
mentioning
confidence: 99%
“…At present, animal models of cystitis are mainly generated by injecting toxic irritants into the bladder of the animals. The toxic irritants include hydrochloric acid, acetic acid, acetone, allyl aldehyde, lipopolysaccharide, protamine sulfate and cyclophosphamide, among which hydrochloric acid is a relatively simple and stable agent that can be used to induce chemical cystitis [22,30]. Previous studies have demonstrated that HCl-induced chemical cystitis in SD rats causes apparent bladder mucosal injury, increased urination time and increased bladder-related pain [23].…”
Section: Discussionmentioning
confidence: 99%
“…This method refers to the previously published protocol of Konkol et al [22]. The animals were anesthetized with 4% chloral hydrate (4% chloral hydrate/rat body weight = 1 ml/100 g).…”
Section: Methods Of Drug Administrationmentioning
confidence: 99%